2018
DOI: 10.7567/apex.11.024101
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of AlGaN/GaN high-electron-mobility transistors electroluminescence characteristics with current collapse

Abstract: We report on the correlation between the electroluminescence and current collapse of AlGaN/GaN high-electron-mobility transistors (HEMTs). Standard passivated devices suffering from severe current collapse exhibited high-intensity whitish electroluminescence confined near the drain contact. In contrast, devices with reduced current collapse resulting from oxygen plasma treatment or GaN capping showed low-intensity reddish emission across the entire gate–drain access region. A qualitative explanation of this ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…HEMTs with high energy hot electrons exhibited a high-intensity whitish EL, whereas HEMTs with relatively low energy hot electrons exhibited a weak reddish EL. [19] On the other hand, in our study, we successfully observed EL color changed from a low-intensity reddish to a high-intensity whitish in one HEMT with increased Vds. [21] These changes in EL color are attributed to a shift of high electric field from the gate to the drain edge.…”
Section: Introductionsupporting
confidence: 49%
See 4 more Smart Citations
“…HEMTs with high energy hot electrons exhibited a high-intensity whitish EL, whereas HEMTs with relatively low energy hot electrons exhibited a weak reddish EL. [19] On the other hand, in our study, we successfully observed EL color changed from a low-intensity reddish to a high-intensity whitish in one HEMT with increased Vds. [21] These changes in EL color are attributed to a shift of high electric field from the gate to the drain edge.…”
Section: Introductionsupporting
confidence: 49%
“…[28] The detectable wavelength range of the SI-CCD camera is 300-1100 nm, so the EL related with the hot electrons in HEMTs can be observed with the PHEMOS ○ R -1000. [19][20] Figures 4 (a emission peak is at the gate. When the Vds increases from 30 to 40 V, the EL of the HEMT shifts 0.5 µm from the gate center toward the drain edge, shown in Fig.…”
Section: Device Fabricationmentioning
confidence: 99%
See 3 more Smart Citations